SATISFACTION OF NON-COVID-19 PATIENTS UNDER NATIONAL HEALTH INSURANCE (JKN) IN CHANGES IN HEALTH SERVICES DURING THE COVID-19 PANDEMIC AND ASSOCIATED FACTORS - Surury, Istianah; Prastiwi, Nastiti Dyah; Ali, Luthfiah Haifah (UI Scholars Hub, 2022)
Currently, health care services follow the first edition of the COVID-19 Prevention Guidelines from the Indonesian Health Ministry. Therefore, health care services should continue to deliver services equally between COVID-19 patients and general patients. Since the onset of the COVID-19 pandemic, a non-COVID-19 patient satisfaction survey has not been conducted at the hospital. Inpatient services are the most affected by COVID-19 because large capacity of bed is allocated for COVID-19. The aims of this study is to determine the level of satisfaction of non-COVID-19 patients under JKN and its associated factors regarding the changes in health care services during the COVID-19 pandemic. This study is observational and quantitative, using primary data with a cross-sectional design study. The sample was 86 people selected using total sampling. The obtained data was analyzed using univariate and bivariate analysis. The result showed there was a relationship between service changes (p=0.000), there was no relationship between age (p=0.254), gender (p=0.183), educational attainment (p=0.528), occupation (p=0,135), JKN membership (p=1,000), inpatient ward class (p=0.168), and satisfication of patients under JKN. Dependent T test analysis obtained a value of 0.000, meaning a significant difference between reality and the patient expectations. The servqual calculation showed the results of gab=-1.05 and an average suitability rate of 71%. The quality of health services is not meeting patient expectations, and changes in services during the COVID-19 pandemic are still not in accordance with the procedures. The hospital is expected to improve the quality of services during the COVID-19 pandemic.